Performance of bentonite and peat moss mixtures as grounding enhancement materials - Wan Ahmad, W. F. H.; Abdul Rahman, A. H.; Jasni, J.; Ab Kadir, M. Z. A. (IEEE, 2023)
Grounding system is one of the lightning protection system that meant to provide protection for a power system, equipment in it and any personnel whom might accidently in touch with it, during both normal and fault conditions. It must with a low impedance path, ensuring all fault currents to be dispersed into earth at the shortest time possible. This could be achieved by treating grounding enhancement materials with the surrounding soil to reduce its earth resistance effectively. Grounding enhancement materials could be natural or chemical based, i.e. CEM and NEM, respectively. Only NEMs were considered in this study where four grounding systems were installed near to SGS, UPM with 100% Bentonite, 100% Peat Moss, Bentonite and Peat Moss Mix A, and Bentonite and Peat Moss Mix B. These NEM were mixed with water for their performances were compared to a Reference grounding system which is without any NEM added to the vicinity of the ground conductor. The performances of all installed grounding systems were evaluated by the percentage reductions of their measured earth resistance values against the Reference grounding system, with Fall-of-potential method, 62% rule and 0 o separation angle were employed. The earth resistances were measured daily for 120 days, i.e. from 1 st Feb 2019 to 1 st Jun 2019 and it has been found that the best performed grounding system in descending order were 100% Bentonite, Bentonite and Peat Moss Mix A, 100% Peat Moss, Bentonite and Peat Moss Mix B, and Reference grounding systems. Note that Bentonite ratio was more in Mix A compared to Mix B.